Transposição Didática da Geometria Diferencial ligada à Cartografia: apoio ao professor de Matemática - Moreno, Thaís Santos (Universidade Federal de São Carlos, 2024)
Theoretically based on Differential Geometry, this writing highlights the relevance of this complex mathematical area and its potential to enrich the Mathematics teaching and learning, especially at more advanced levels. By studying Differential Geometry, it was possible to establish a connection between this content and elementary education, especially in the artography study, whose skill is included in the National Common Curricular Base (BNCC). Connection between Differential Geometry and Cartography aims to provide broader and more contextualized theoretical support to the teacher. Didactic Transposition is explored as an important strategy for this integration. Through it, it is possible to translate the abstract concepts of Differential Geometry into a language accessible to students, making the educational process more meaningful. The developed class plan offers ideas to improve pedagogical practice, highlighting the expressive role of the teacher when preparing their classes, not only as a transmitter of knowledge, but as a learning process facilitator, promoting interdisciplinary connections and stimulating critical thinking and creativity of students.
Didactic Transposition of Differential Geometry linked to Cartography: Math teacher support
Keywords: Geometria Diferencial; Cartografia; Plano de aula; Transposição Didática; Differential Geometry; Cartography; Class Plan; Didactic Transposition; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA